2020
DOI: 10.3389/fmicb.2020.615404
|View full text |Cite
|
Sign up to set email alerts
|

Algal Oil Rich in n-3 PUFA Alleviates DSS-Induced Colitis via Regulation of Gut Microbiota and Restoration of Intestinal Barrier

Abstract: Algal oil is rich in docosahexaenoic acid (DHA) and has various health benefits against human metabolic disorders and disease. This study aimed to investigate the effects of DHA algal oil on colonic inflammation and intestinal microbiota in dextran sulfate sodium (DSS)-induced colitis mice model. Male C57BL/6 mice was induced colitis by 2.5% DSS and followed by 2 weeks of treatment with algal oil (250 or 500 mg/kg/day). The colonic inflammation was assessed by colon macroscopic damage scores, and the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Maintaining the normal expression of TJ proteins and the permeability of the intestinal epithelial barrier may be a crucial target for the treatment of IBD. Consistent with the previous results, the protein expression of claudin-1, occludin, and ZO-1 decreased after treatment with DSS [34]. However, treatment with the GPH extracts significantly increased the expression of the three TJ proteins, possibly due to the richness of flavonoids in the extracts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Maintaining the normal expression of TJ proteins and the permeability of the intestinal epithelial barrier may be a crucial target for the treatment of IBD. Consistent with the previous results, the protein expression of claudin-1, occludin, and ZO-1 decreased after treatment with DSS [34]. However, treatment with the GPH extracts significantly increased the expression of the three TJ proteins, possibly due to the richness of flavonoids in the extracts.…”
Section: Discussionsupporting
confidence: 90%
“…A large number of studies have shown that IBD is related to the imbalance of intestinal immunity and inflammatory factors, such as IL-6, IL-1β and TNF-α, which are involved in the destruction of TJ proteins and are regulated by the NF-kB signaling pathway [2,31,34]. Therefore, controlling the production and release of inflammatory cytokines is considered a potential strategy for the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This again indicates that the combination diet balances the effects of scGOS:lcFOS and n-3 PUFAs, which might be of valuable interest when combining these components in a healthy host or in models of disease. The main impact of n-3 PUFAs in this study was the modulated intestinal microbiota, which match finding of other studies [ 89 , 103 ]. To be able to explain the results, data on the n-3 PUFA metabolites in blood and/or brain tissues might have been useful.…”
Section: Discussionsupporting
confidence: 92%
“…These alternative therapies are of great interest because of their low side effects [7]. Among these, algal oil [8], propolis extract [9], peptides derived from tuna [10], taurine [11], and astragalin [12] have been reported to exert protective effects against experimental colitis induced by dextran sulfate sodium (DSS) in mice. Thus, the potential exists for IBD patients to have a greater variety of substances that are effective, in the form of alternative treatments.…”
Section: Introductionmentioning
confidence: 99%